Quantified Audiences in News Production: A synthesis and research agenda. Issue 4 (21st April 2018) - Zamith, Rodrigo
Abstract : A number of social, technological, and economic shifts over the past two decades have led to the proliferation of audience analytics and metrics in journalism. This article contends that we are witnessing a third wave toward the rationalization of audience understanding and distinguishes between audience analytics (systems that capture information) and audience metrics (quantified measures output by those systems). The body of literature on analytics and metrics in the context of news production is then synthesized across the ABCDE of news production: attitudes, behaviors, content, discourse, and ethics. That synthesis leads to an overarching conclusion that while contemporary journalism is not being driven by quantified audiences, both audiences and quantification are playing far more prominent roles in news production than in the past. Scholars and practitioners have also become less pessimistic about analytics and metrics over time, recognizing more nuanced effects and prosocial possibilities. Finally, important gaps in the literature are identified and new research directions proposed to help address them.